Nb and Ni Nanoparticles Anchored on N-Doped Carbon Nanofiber Membrane as Self-Supporting Anode for High-Rate Lithium-Ion Batteries - Yezheng Zhang; Shan Zhang; Shuo Zhao; Yingxue Cui; Jiabiao Lian; Guochun Li (Nanomaterials, 2022)
A flexible N-doped carbon nanofiber membrane loaded with Nb and Ni nanoparticles (Nb/Ni@NC) was prepared using electrospinning technology and a subsequent thermal annealing method and used as a self-supporting anode material for lithium-ion batteries. The Nb/Ni@NC nanofiber membrane had excellent flexibility and could be folded and bent at will without fragmentation and wrinkling; the nanofibers also had a uniform and controllable morphology with a diameter of 300–400 nm. The electrochemical results showed that the flexible Nb/Ni@NC electrode could deliver a high discharge capacity of 378.7 mAh g−1 after 200 cycles at 0.2 A g−1 and an initial coulombic efficiency of 67.7%, which was higher than that of the pure flexible NC anode in contrast. Moreover, a reversible discharge capacity of 203.6 mAh g−1 after 480 cycles at 1.0 A g−1 was achieved by the flexible Nb/Ni@NC electrode with a capacity decay for each cycle of only 0.075%, which showed an excellent rate capability and cycling stability.